Oxford and Cambridge Boat Race: Performance, pacing and tactics between 1890 and 2014 - Edwards, A. M.; Guy, J. H.; Hettinga, F. J. (Sports Medicine, 2016)
Background: Currently no studies have examined the historical performances of Oxford and Cambridge Boat Race crews in the context of performance, pacing and tactics which is surprising as the event has routinely taken place annually for over 150 years on the same course. Objectives: The purpose of this study was twofold, to firstly examine the historical development of performances and physical characteristics of crews over 124 years of the Oxford and Cambridge Boat Race between 1890 and 2014 and secondly to investigate the pacing and tactics employed by crews over that period. Methods: Linear regression modelling was applied to investigate the development of performance and body size for crews of eight male individuals over time from Boat Race archive data. Performance change over time was further assessed in 10-year clusters while four intra-race checkpoints were used to examine pacing and tactics. Results: Significant correlations were observed between performance and time (1890-2014) for both Oxford (r = -0.67; p < 0.01) and Cambridge (r = -0.64; p < 0.01). There was no difference in mean performance times for Oxford (1170 ± 88 s) and Cambridge (1168 ± 89.8 s) during 1890-2014. Crew performance times improved over time with significant gains from baseline achieved in the 1950s (Cambridge) and the 1960s (Oxford), which coincided with significant change in the physicality of the competing crews (p < 0.01). There was no tactical advantage from commencing on either the Surrey or Middlesex station beyond chance alone; however, all crews (n = 228) adopted a fast-start strategy, with 81 % of victories achieved by the crew leading the race at the first intra-race checkpoint (24 % of total distance). Crews leading the race at the final checkpoint (83 % of total distance; 1143 m) achieved victory on 94 % of occasions. Conclusion: Performances and physical characteristics of the crews have changed markedly since 1890, with faster heavier crews now common. Tactically, gaining the early lead position with a fast-start strategy seems particularly meaningful to success in the Boat Race throughout the years, and has been of greater importance to race outcome than factors such as the starting station.